2000
DOI: 10.1021/es991331i
|View full text |Cite
|
Sign up to set email alerts
|

Stability of Immobilized TNT Derivatives in Soil as a Function of Nitro Group Reduction

Abstract: The stability of soil bound metabolites of 2,4,6-trinitrotoluene (TNT) was investigated. Highly TNT-contaminated soil from a former production site was spiked with [ring-UL-14C]TNT. An anaerobic short-term treatment (8 days) was carried out and compared with a previously described long-term anaerobic (51 day) treatment. In the short-term experiment the anaerobic treatment was stopped to examine the early-stage effects of the reduction process on the stability of TNT derivatives in soil at the time of the maxim… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
25
1

Year Published

2004
2004
2012
2012

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 35 publications
(26 citation statements)
references
References 36 publications
0
25
1
Order By: Relevance
“…The metabolites 2-amino-4,6-dinitrotoluene and 4-amino-2,6dinitrotoluene that generally are observed in similar soil experiments were detected only transiently in amounts Յ3% of the applied TNT. During anaerobic treatments of TNT-contaminated soils, ADNT and DANT initially were detected in amounts one order of magnitude higher than after aerobic treatments [6,7]. Formylated or acetylated metabolites known from fungal metabolism of TNT [5], as well as HADNT, were not detected in the present experiments.…”
Section: Resultscontrasting
confidence: 71%
“…The metabolites 2-amino-4,6-dinitrotoluene and 4-amino-2,6dinitrotoluene that generally are observed in similar soil experiments were detected only transiently in amounts Յ3% of the applied TNT. During anaerobic treatments of TNT-contaminated soils, ADNT and DANT initially were detected in amounts one order of magnitude higher than after aerobic treatments [6,7]. Formylated or acetylated metabolites known from fungal metabolism of TNT [5], as well as HADNT, were not detected in the present experiments.…”
Section: Resultscontrasting
confidence: 71%
“…With smectite clays, the binding of the nitro groups of TNT essentially replace the calcium in the clay matrix, thus integrating the energetic ). Under anoxic conditions in water, the nitro groups of TNT can be reduced to amines (Barrows et al 1996) which also affects its reactivity (Achtnich et al 2000). The presence of reduced colloidal or particulate iron (ZVI) can also reduce these nitro groups and enhance both the reactivity and mineralization of TNT in aqueous environments (Agrawal and Tratnyek 1996, Devlin et al 1998, Brannon et al 2002 though transformation rates based on laboratory experiments may overestimate the expected rates in the field (Bandstra et al 2005).…”
Section: Abiotic -Chemicalmentioning
confidence: 99%
“…Intercalation of nitroanilines into kaolinite was studied in the work of Takenawa et al [31]. The results of several experimental investigations of interactions of soils with explosives, especially with nitroaromatic explosives, using several physicochemical methods, were recently published [33][34][35][36][37][38][39][40][41]. Townsend and Myers [33] found that the major factor affecting the fate and transport of TNT in the subsurface were transformation, sorption, and irreversible soil binding.…”
Section: Introductionmentioning
confidence: 99%